2011
DOI: 10.4061/2011/593624
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Production and Optimization of Alkaline Xylanase by Indigenous Bacillus mojavensis AG137 Fermented on Agricultural Waste

Abstract: A xylanase producer Bacillus mojavensis strain, called AG137, isolated from cotton farm (Kashan-Iran). The optimal xylanase activity reached at 55°C & pH 9.0. Enzyme yield was studied using a medium with different agricultural wastes as inducers. Xylanase production of about 249.308 IU/mL was achieved at pH 8 and 37°C, within 48 h submerged fermentation in enzyme production medium supplemented with 2% (w/v) oat bran as an optimum carbon source. A mixture of 1% (w/v) yeast extract and 1% (w/v) tryptone as optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 23 publications
2
24
1
1
Order By: Relevance
“…Similar finding to this study was made by other authors who reported 30°C as optimal temperature for xylanase and cellulase production by different Bacillus species (Nagar et al, 2012;Bai et al, 2012;; and very close to the finding of Mukesh who reported that 32°C was optimal for cellulase production by B. cereus MRK1. Contrary to the result of this study however, maximum production of xylanase and cellulase by other bacterial species at both lower and higher incubation temperatures have been reported (Sepahy et al, 2011;Bibi et al, 2014), which is suggestive that optimal incubation temperature for cellulase and xylanase production is dependent on bacterial strain (Gautam et al, 2011).…”
Section: Effect Of Incubation Temperaturecontrasting
confidence: 55%
See 2 more Smart Citations
“…Similar finding to this study was made by other authors who reported 30°C as optimal temperature for xylanase and cellulase production by different Bacillus species (Nagar et al, 2012;Bai et al, 2012;; and very close to the finding of Mukesh who reported that 32°C was optimal for cellulase production by B. cereus MRK1. Contrary to the result of this study however, maximum production of xylanase and cellulase by other bacterial species at both lower and higher incubation temperatures have been reported (Sepahy et al, 2011;Bibi et al, 2014), which is suggestive that optimal incubation temperature for cellulase and xylanase production is dependent on bacterial strain (Gautam et al, 2011).…”
Section: Effect Of Incubation Temperaturecontrasting
confidence: 55%
“…Several Bacillus species includig B. circulans, B. amyloliquefaciens, B. halodurans, B. licheniformis, B. subtilis and B. mojavensis have been reported as producers of cellulase and xylanase (Ray et al, 2007;van Dyk et al, 2010;Sepahy et al, 2011;Acharya and Chaudhary, 2012). However, investigation of hemi (cellulolytic) bacteria from marine environment is on the increase due to their remarkable versatility and adaptation to heterogeneous environmental conditions (Lordan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ab 106. On the contrary, Sepahy et al [51] reported 200 rpm as optimal for xylanase production by Bacillus mojavensis AG137 cultured on agricultural waste. Whereas Saratale et al [31] reported static condition as optimal for endocellulase production by Streptomyces sp.…”
Section: Effect Of Agitation On Cellulase and Xylanase Productionmentioning
confidence: 96%
“…However, increasing the production period failed to increase the levels of enzymatic activity. On the contrary, they would rather be reduced, suggesting the hypothesis that decrease was caused by depletion of nutrients or proteolysis due to secretion of nonspecific proteases (Sepahy, Ghazi, & Sepahy, 2011;Nasr, Soudi, Salmanian, & Ghadam, 2013).…”
Section: Discussionmentioning
confidence: 99%